Positional changes of maxillary central incisors following orthodontic treatment using single‐crown implants as fixed reference markers. Issue 12 (18th June 2017) - Brahem, E. B.; Holm, B.; Sonnesen, L.; Worsaae, N.; Gotfredsen, K.
Abstract: Objectives: This follow‐up study (1) compares tooth displacement of central incisors in patients with and without pre‐implant orthodontic treatment and (2) investigates whether sex, age, or orthodontic retention have an effect on tooth displacement after the insertion of single‐crown implants. Materials and Methods: Fifty‐seven patients – thirty‐seven with (test group) and twenty without pre‐implant orthodontic treatment (control group) – were rehabilitated with 89 single‐crown implants in the upper maxilla. Clinical and radiographic data, clinical photographs, and dental casts were collected during baseline examinations after prosthetic rehabilitation and at the final follow‐up examination at least 5 years later. A total of 114 dental casts were digitalized and aligned using a software program to measure changes in the positions of the central incisors. Results: After a follow‐up period of at least five years, 87% of the central incisors measured in the test group were displaced >0.25 mm vertically compared with 70% in the control group. Seventy‐eight percent of the test group teeth had moved >0.25 mm horizontally compared with 55% in the control group. These differences were not significant, and there were no significant correlations with patient age or sex. Conclusion: The majority of patients had minor vertical (60%) or horizontal (67%) tooth displacement of the central incisors (0.25–0.75 mm) after a minimum follow‐up period of 5 years. This study found no significant differences in tooth displacement comparing patients with and without pre‐implant orthodontic treatment. No significant effect of sex, age, orthodontic retention, or implant location was observed on tooth displacement.